To simplify the expression \( 122 - 3 \times 4^2 + \sqrt{4} - 3 \), let's follow the order of operations (PEMDAS/BODMAS).
-
Calculate \( 4^2 \): \[ 4^2 = 16 \]
-
Calculate \( 3 \times 16 \): \[ 3 \times 16 = 48 \]
-
Calculate \( \sqrt{4} \): \[ \sqrt{4} = 2 \]
Now, substitute these values back into the expression: \[ 122 - 48 + 2 - 3 \]
- Now perform the operations from left to right:
-
First, calculate \( 122 - 48 \): \[ 122 - 48 = 74 \]
-
Next, add \( 2 \): \[ 74 + 2 = 76 \]
-
Finally, subtract \( 3 \): \[ 76 - 3 = 73 \]
-
Thus, the simplified result of the expression is: \[ \boxed{73} \]